Practical business math procedures - Slater, Jeffrey, 1947-; Slater, Jeffrey, 1947- (Homewood, IL : Irwin, 1991)
'Business math and its applications are continually around you, Knowing facts based on business math often affect many of your daily decisions." This introduction on business decision making should inspire you to learn more about business math topics in this book, you should review your basic math computational skills and for speed and accuracy."
Four folded pages in pocket.
Accompanied by: Business math handbook / Jeffrey Slater. 60 p. ; 28 cm.
Includes index.
English text.
Keywords: Business mathematics -- Problems, exercises, etc